Real-Time Observations of Food and Fluid Timing During a 120 km Ultramarathon - Wardenaar, Floris C.; Hoogervorst, Daan; Versteegen, Joline J.; van der Burg, Nancy; Lambrechtse, Karin J.; Bongers, Coen C. W. G. (Frontiers in Nutrition, 2018)
The aim of the present case study was to use real-time observations to investigate ultramarathon runners' timing of food and fluid intake per 15 km and per hour, and total bodyweight loss due to dehydration. The study included 5 male ultramarathon runners observed during a 120 km race. The research team members followed on a bicycle and continuously observed their dietary intake using action cameras. Hourly carbohydrate intake ranged between 22.1 and 62.6 g/h, and fluid intake varied between 260 and 603 mL/h. These numbers remained relatively stable over the course of the ultra-endurance marathon. Runners consumed food and fluid on average 3–6 times per 15 km. Runners achieved a higher total carbohydrate consumption in the second half of the race (p = 0.043), but no higher fluid intake (p = 0.08). Energy gels contributed the most to the total average carbohydrate intake (40.2 ± 25.7%). Post-race weight was 3.6 ± 2.3% (range 0.3–5.7%) lower than pre-race weight, revealing a non-significant (p = 0.08) but practical relevant difference. In conclusion, runners were able to maintain a constant timing of food and fluid intake during competition but adjusted their food choices in the second half of the race. The large variation in fluid and carbohydrate intake indicate that recommendations need to be individualized to further optimize personal intakes.